Vibrating Reed Study of Superconducting Cuprates Fabricated by Superfast Melt Quenching in a Solar Furnace - Chigvinadze, J.; Tavkhelidze, V.; Mamniashvili, G.; Donadze, G.; Acrivos, J. V.; Gulamova, D. (Engineering, Technology & Applied Science Research, 2019)
In this study, the potential possibilities of the precision of the vibrating reed method for the evaluation of the Тс of superconducting precursors in an HTSC Bi-Pb-Sr-Cu-O system were investigated. A special technology for obtaining these samples by using solar energy for melting and following superfast melt quenching was applied to increase their internal inhomogeneity, allowing to receive high-quality textural ceramic samples of Bi1,7Pb0,3Sr2Can-1CunOy (n=2-30) showing critical temperatures of superconducting precursor transitions above bulk Тс. To determine critical temperatures of superconducting precursors above bulk Тс for the first time, the original vibrating reed method of studying these multiphase samples in an applied magnetic field was used. It was shown that this method has sensitivity to superconducting diamagnetism making possible to reveal new superconducting precursor phases above bulk Tc.